Evaluating Medical Student and Resident Performance - Paul Ogden (Association of American Medical Colleges, 2006)
Abstract These four videos were originally part of an interactive tutorial for faculty describing defined standards for evaluation of medical student and residents. The tutorial also covered evaluation in general, including the importance of objective performance assessment, changing the faculty role from mentor to judge/diagnostician for evaluation, and several practice cases using the RIME (Reporter, Interpreter, Manager, Educator) system described by Pangaro et al. These videos depict conversations between medical students or residents giving their case diagnoses and the doctor evaluating them.